2019
DOI: 10.1142/s0219199718500475
|View full text |Cite
|
Sign up to set email alerts
|

A continuous time tug-of-war game for parabolic p(x,t)-Laplace-type equations

Abstract: We formulate a stochastic differential game in continuous time that represents the unique viscosity solution to a terminal value problem for a parabolic partial differential equation involving the normalized [Formula: see text]-Laplace operator. Our game is formulated in a way that covers the full range [Formula: see text]. Furthermore, we prove the uniqueness of viscosity solutions to our equation in the whole space under suitable assumptions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In the tug-of-war game, when one takes into account the number of plays that the players play and considering sets of possible movements that may depend on space and time, the continuum value function will be the solution of the parabolic equation involved infinity Laplacian. See the details for example [22,32] and the references therein.…”
Section: Introductionmentioning
confidence: 99%
“…In the tug-of-war game, when one takes into account the number of plays that the players play and considering sets of possible movements that may depend on space and time, the continuum value function will be the solution of the parabolic equation involved infinity Laplacian. See the details for example [22,32] and the references therein.…”
Section: Introductionmentioning
confidence: 99%
“…As interpreted in [15,29], parabolic equations of the type considered in (1.1) arise naturally from a two-player zero-sum stochastic differential game (SDG) with probabilities depending on space and time. It is defined in terms of an n-dimensional state process, and is driven by a 2n-dimensional Brownian motion for n ≥ 2.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Parviainen-Ruosteenoja [29] proved the Hölder and Harnack estimates for a more general game that was called p(x, t)-game without using the PDE techniques and showed that the value functions of the game converge to the unique viscosity solution of the Dirichlet problem to the normalized p(x, t)-parabolic equation (n + p(x, t))u t (x, t) = ∆ N p(x,t) u(x, t). In addition, Heino [15] formulated a stochastic differential game in continuous time and obtained that the viscosity solution to a terminal value problem involving the parabolic normalized p(x, t)-Laplace operator is unique under suitable assumptions. However, whether or not the spatial gradient ∇u of (1.1) is Hölder continuous was still unknown.…”
Section: Introductionmentioning
confidence: 99%